2022
DOI: 10.3390/ijms23094769
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the NAC Gene Family in Zanthoxylum bungeanum and Their Transcriptional Responses to Drought Stress

Abstract: NAC (NAM, ATAF1/2, and CUC2) transcription factors (TFs) are one of the largest plant-specific TF families and play a pivotal role in adaptation to abiotic stresses. The genome-wide analysis of NAC TFs is still absent in Zanthoxylum bungeanum. Here, 109 ZbNAC proteins were identified from the Z. bungeanum genome and were classified into four groups with Arabidopsis NAC proteins. The 109 ZbNAC genes were unevenly distributed on 46 chromosomes and included 4 tandem duplication events and 17 segmental duplication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…There is ample evidence to suggest that the NAC gene family already existed in early plants such as moss and ferns, and its origin is closely related to the formation of the multicellular structure and complex life cycle of plants ( Hu et al, 2022 ; Yang et al, 2023 ). The expansion of the NAC gene family is mainly achieved through gene duplication and selective preservation ( Diao et al, 2018 ; Jin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ample evidence to suggest that the NAC gene family already existed in early plants such as moss and ferns, and its origin is closely related to the formation of the multicellular structure and complex life cycle of plants ( Hu et al, 2022 ; Yang et al, 2023 ). The expansion of the NAC gene family is mainly achieved through gene duplication and selective preservation ( Diao et al, 2018 ; Jin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The structure domain of NAC is mainly located in the DNA binding region, consisting of approximately 150 amino acid residues, which further form five functionally diverse subdomains based on conservation ( Jensen et al, 2010 ; Puranik et al, 2012 ). At present, the NAC TF has been characterized in numerous species, such as Arabidopsis thaliana ( Lindemose et al, 2014 ), Oryza sativa ( Nuruzzaman et al, 2010 ), Glycine max ( Singh et al, 2021 ), Capsicum annuum ( Diao et al, 2018 ), Brassica rapa ( Liu et al, 2014 ), Zanthoxylum bungeanum ( Hu et al, 2022 ), and Camellia sinensis ( Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of high-throughput DNA sequencing technology has ushered in a rapid expansion in the sequencing of plant genomes, thereby facilitating genome-wide investigations into the NAC gene family across various plant species. So far, the extensive identification and analysis of the NAC gene family have been conducted in a range of model plants and crop species, including A. thaliana [25], Oryza sativa [26], Vigna radiata [27], Capsicum annuum [28], and Zanthoxylum bungeanum [29]. NAC TFs may play an important role in the environmental stress tolerance of stress-tolerant wild plants, but there is currently insufficient research on the NAC genes of stress-tolerant wild plants.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, research on NAC transcription factors is continuing. Some studies have identified and analyzed members of the NAC gene family in plant genomes such as Arabidopsis thaliana ( Hisako et al., 2004 ), Zanthoxylum bungeanum ( Hu et al., 2022 ), potato ( Singh et al., 2013 ), melon ( Wei et al., 2016 ), sunflower ( Bengoa Luoni et al., 2021 ), Asparagus officinalis ( Li C. et al., 2022 ), Brassica juncea var. Tumida ( He et al., 2020 ), Saccharum spontaneum ( Shen et al., 2022 ) and Hibiscus hamabo Sieb ( Wang et al., 2022b ), but there is no relevant research report on the NAC gene family in D. nobile ’s whole genome.…”
Section: Introductionmentioning
confidence: 99%